Korean Lacquerware from the Late Joseon Dynasty: Conservation and Analysis of Four Objects at the Asian Art Museum of San Francisco. (17th February 2023) - O'Shea, Colleen; Fenn, Mark; Gillis, Kathy Z.; Khanjian, Herant; Schilling, Michael
ABSTRACT: In-depth studies of the manufacture and composition of late nineteenth century Korean lacquerware from the Joseon dynasty are underrepresented in the English-language literature. This article, the first to offer a comprehensive layer-by-layer analysis of late Joseon dynasty lacquerware, shows that these objects are made using a mixture of traditional lacquerware techniques and materials together with new materials and methods. Through conservation and analysis of four lacquerware objects from the exhibition Mother-of-Pearl Lacquerware from Korea at the Asian Art Museum (29 April–23 October 2016), we identify the materials and techniques used in manufacture and present a new technique to allow conservators to compensate for losses of ray skin inlay. Our discovery that artists used shellac at multiple stages during manufacture calls into question the assumption that shellac was used only as a surface coating. Our findings demonstrate the material and technological complexity of Korean lacquerware from this period and can inform efforts at conservation and analysis of similar objects.